MTA APICAL PLUG AND CLINICAL APPLICATION OF ANATOMIC POST AND CORE FOR CORONAL RESTORATION: A CASE REPORT - kumar, RAHUL; Patil, Suvarna; Hoshing, Upendra; Medha, Ashish; Mahaparale, Rushikesh (Iranian Endodontic Journal, 2011)
ABSTRACT: Apexification with calcium hydroxide is associated with certain difficulties, such as longer treatment time, risk of tooth fracture and incomplete calcification of apical bridge. Mineral trioxide aggregate (MTA) is an alternative material that can be used for apexification of open apices due to its biocompatibility, non-mutagenicity, non-neurotoxicity, regenerative abilities, and good sealing properties. This case report demonstrates application of MTA apical plug and anatomic post and core for the reconstruction of maxillary central incisor. The patient was recalled after six months and no complications were noted. Periapical radiographs demonstrated good adaptation of anatomical post and core to post space and the complete healing of the periapical lesion. This new technique is particularly advantageous in teeth which have open apex, root canals that are not round, wide canals and thin radicular dentin. It is also useful for who request in patients fewer visits.